Association of sarcopenia, ambient air pollution and cognitive function in a community-dwelling middle-aged and elderly Korean population: a community-based cohort study - Ji Hyun Kim; Kyoungho Lee; Jane J Lee; Hae Dong Woo; Eun Ju Jung (BMJ Open)
Objectives To investigate the association of sarcopenia, exposure to medium-term to long-term ambient particulate matter 2.5 µm and 10 µm (PM2.5 and PM10) pollution and cognitive function in a community-dwelling cohort of middle-aged and older adults in South Korea.Design A community-based prospective cohort study.Setting In the Korean Genome and Epidemiology Study (KoGES).Participants The participants were drawn from the seventh follow-up visit conducted between 2015 and 2016 in the KoGES community-based Ansung cohort who had participated in an ageing substudy.Outcome measures Cognitive function was evaluated by the Korean version of the Mini-Mental State Examination (K-MMSE) and decreased cognitive function was defined as a K-MMSE score of 23 or less.Results Of the 2274 participants (mean age 70.1 years, 58.3% women and mean annual PM2.5 and PM10 levels of 30.7 and 52.2 μg/m3, respectively), 8.7% (n=197) were sarcopenic, 35.8% (n=814) were possible sarcopenic and 55.5% (n=1263) were non-sarcopenic. The predictors of sarcopenia included body mass index, cognitive function, age, marital status, hypertension and physical activity. Exposure to PM2.5 and PM10 for an average duration of 1 month to 3 years was not selected as a predictor of sarcopenia. Participants with sarcopenia were associated with lower cognitive scores (β=−1.51, p<0.0001) and decreased cognitive function compared with those without sarcopenia (OR 2.34, 95% CI 1.56 to 3.52). Exposure to medium-term and long-term PM2.5 or PM10 was not associated with sarcopenia. The effect modification of PM exposure on the association between sarcopenia and cognitive function was generally not detected.Conclusions In this community-based observational cohort study of KoGES participants aged 50 years and older, sarcopenia was associated with decreased cognitive function. However, medium-term to long-term exposure to PM2.5 or PM10 was not associated with sarcopenia and did not modify the relationship between sarcopenia and cognitive function.